The Importance of Community Involvement in Public Management Planning and Decision-Making Processes - Rijal, Syamsu (ADMAN: Journal of Contemporary Administration and Management, 2023)
Public management is an effort to deliver public services, programmes, and projects that are efficient, effective, and equitable for the community. The planning and decision-making processes of public management are two key aspects in achieving this goal. Traditionally, the planning and decision-making processes of public management are mostly carried out by government officials and internal stakeholders without involving active participation from the community. However, in this increasingly complex and diverse era, community involvement is important and cannot be ignored. This research aims to explore the role of the community in public decision-making and its impact on efficiency, effectiveness and fairness in public service delivery. This research is a literature review that adopts a qualitative method approach, which means it will analyse and interpret data by relying on information and text from various sources. The study results show that community involvement in the planning and decision-making process of public management is a key principle in democratic and participation-based governance. Community participation helps to create a government that is more transparent, accountable, inclusive, and responsive to the needs and aspirations of the people.